2001
DOI: 10.1177/004947550103100218
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia in Rural Tanzania

Abstract: A survey of the anaesthetic services in rural Tanzania was carried out in an area of 67500 km2 and population of 4 million in order to assess the quality of anaesthesia and the major obstacles to good practice. Lack of draw-over vaporizers, Ayre's T-pieces, and a supply of oxygen were found to be the major obstacles to safe practice in this area of Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Unfortunately, because the disparity in quality of care within developing countries is wide [2], no reliable comparative epidemiological data of critical illness syndromes, such as acute lung injury and sepsis, are available. While respiratory failure may be fairly easy to diagnose clinically (such as hypoxia or increased work of breathing), it is a consequence of a primary disease process (ie, pneumonia) – thus, as a secondary process, collection of epidemiologic data are challenging in resource–poor settings.…”
Section: Burden Of Respiratory Failure In Developing Countries: a Chamentioning
confidence: 99%
“…Unfortunately, because the disparity in quality of care within developing countries is wide [2], no reliable comparative epidemiological data of critical illness syndromes, such as acute lung injury and sepsis, are available. While respiratory failure may be fairly easy to diagnose clinically (such as hypoxia or increased work of breathing), it is a consequence of a primary disease process (ie, pneumonia) – thus, as a secondary process, collection of epidemiologic data are challenging in resource–poor settings.…”
Section: Burden Of Respiratory Failure In Developing Countries: a Chamentioning
confidence: 99%
“…In one region of Tanzania serving four million people, Kimaro showed that only nine hospitals of 27 could give endotracheal anesthesia to an adult and a child with the use of oxygen. 25 In Guinea-Bissau, none of the operating rooms of eight hospitals surveyed had pulse oximeters; only two of eight hospitals had electrocardiography devices (P. Baele: personal communication).…”
Section: Resourcesmentioning
confidence: 99%
“…Except in cases of war or natural catastrophes, the majority of hospitals have access to water and electricity (33). Power supply in many LDCs is characterized by intermittent voltage peaks (up to 500 -600 V), which prohibit usage of electronic medical devices without an upstream voltage stabilizer (34).…”
Section: Infrastructurementioning
confidence: 99%